2017
DOI: 10.1007/s00590-017-2100-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of active straight leg raising, standing up, and walking after total knee arthroplasty in a cross-sectional study

Abstract: Prognostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Our study’s findings, however, differ from a cross-sectional study by Ishii et al which found no significant correlation between time to SLR and time to ambulation. 18 This could be due to population differences in terms of ethnicity and body mass index. Early mobilization after TKA has been established to influence LOS and it could indicate better functional recovery, as patients with early mobilization were more likely to be discharged to home compared to sub-acute rehabilitation facility.…”
Section: Discussionmentioning
confidence: 99%
“…Our study’s findings, however, differ from a cross-sectional study by Ishii et al which found no significant correlation between time to SLR and time to ambulation. 18 This could be due to population differences in terms of ethnicity and body mass index. Early mobilization after TKA has been established to influence LOS and it could indicate better functional recovery, as patients with early mobilization were more likely to be discharged to home compared to sub-acute rehabilitation facility.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability parameters were reported for almost all physical tests. The strength testing of knee flexor/extensor by isometric or isokinetic dynamometer (strength) [ 87 ], 6-min Walk Test (6MWT) [ 9 , 54 , 91 ], Five Times Sit-To-Stand Test (5STS test) [ 43 , 64 , 92 ], Timed Up and Go Test (TUG) [ 2 , 43 , 54 , 91 , 93 ] and Stair Climbing Time (SCT) [ 6 , 94 , 95 ] test had positive ratings for both intra- and inter-tester reliability. The Pressure Pain Threshold (PPT) [ 86 ] had a positive rating for intra-tester reliability, but inter-tester reliability was not assessed.…”
Section: Resultsmentioning
confidence: 99%
“…For 6 (50%) tests, interpretability was rated positive for the knee range of motion [ 48 , 55 ], strength [ 87 ], PPT [ 86 ], 6MWT [ 9 , 54 , 91 ], 5STS [ 43 , 64 , 92 ] and TUG [ 2 , 43 , 54 , 91 , 93 ] tools. The remaining tools had doubtful or no ratings mostly due to lack of MDC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations